Exploration in Synthesis and Fungicidal Activities of Some Novel O-Ethyl O-Heteroaryl 2-Chloroethyl Phosphonates - ATULYA KUMAR PANDA (International Journal of Pharma and Bio Sciences, 2010)
Novel O-ethyl O-heteroaryl 2-chloroethyl phosphonates have been prepared by condensing 2-chloroethyl phosphonyl dichloride by the sequential addition of ethanol and –OH and –SH carrying heteroaryls. Attempts of the above reaction with –NH carrying heteroaryl (benzimidazole) furnished a different product than the expected one by different reaction path.